Wilder Ways - Jackson, Donald C. (Book collections on Project MUSE., 2012)
In Wilder Ways, Donald C. Jackson takes readers on a journey into the deep and very personal connections that can develop between people and wild places while hunting, fishing, and rambling across landscapes. Fishing by lantern light late at night for bullhead catfish on a small stream, hunting wood ducks and squirrels on his farm in north Mississippi, bow hunting deer as twilight creeps across a small clearing, handlining crabs in the Pascagoula River estuary, hunting caribou in Alaska and elk in Colorado, searching for blind fish in Ozark caves, and fighting a storm on an Indonesian river: J.